Modernity and English mixing: A study of Nepali television commercials - Acharya, Khagendra (Bodhi: An Interdisciplinary Journal, 2010)
In this paper, I investigate the issue of English mixing in Nepali television commercials. More specifically, based on qualitative data taken from a total of four hours of Nepali TV commercials broadcasted on the major Nepali television stations - Avenues Television and Kantipur Television from 7am to 9am and 7pm to 9pm since 1 July to 1 October 2009, I examine the motivations for English mixing in Nepali TV commercials. For the analysis, primarily I categorize them into two major types, Nepali-only (NO) and English mixed (EM). NO includes commercials aired in Nepali only and EM includes advertisements aired in Nepali in juxtaposition with English. After it, I study the differences between EM and NO as the dichotomous treatment of NO and EM is critical in examining the purpose of English-mixing. The findings suggest that English-mixing in Nepalese TV commercials is a carefully constructed exemplar of the marketing of modernity. DOI: 10.3126/bodhi.v3i1.2812 Bodhi Vol.3(1) 2009 p.53-60